Gambaran Patologi Embrio Ayam yang Terinfeksi Avian orthoreovirus Isolat Lokal - Putra, Raditya Pradana; Murtini, Sri; Poetri, Okti Nadia (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2024)
Avian orthoreovirus (ARV) is widespread and found in almost every commercial poultry farm and other poultry species. Virus isolation from local isolates is necessary to obtain vaccine seeds that are homologous to viruses in the field.  The R&D Laboratory of PT Vaksindo Satwa Nusantara successfully isolated ARV from field cases. Inoculation of SPF Embryonated Chicken Eggs (ECE) is the protocol used to evaluate virus titer, especially to calculate the antigen titer of vaccine prototype candidates. The gross pathology of chicken embryos infected with ARV to evaluate virus growth has not been widely reported. This study aims to observe the gross pathology of chicken embryos infected with ARV to measure the virus titer using infectivity test such as the embryo infectious dose 50 (EID50). The virus suspension was diluted from 10-1 to 10-6 then dilutions of 10-4 to 10-6 were inoculated each into five ECE. Incubated ten days and observed for embryonic death. The observations found the embryonic death on day seven. Pathological changes in the embryos are stunted, thin feather, oedema, and less allantois fluid compared to control of uninfected embryo. The results of the embryos necropsy showed cardiac necrosis, greenish liver, and gelatinous exudate in the abdominal cavity.Keywords - Avian Orthoreovirus, Embryonated Chicken Eggs, Embryo Pathology, EID50.